Pengaruh Kompetensi dan Pengembangan Karir terhadap Kinerja Pegawai Sekretariat Badan Perkembangan Sumber Daya Manusia (BPSDM) Perhubungan Jakarta - Hery Santosa (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Employee performance is a crucial factor in supporting organizational effectiveness, particularly in public institutions responsible for human resource development. Competence and career development are considered important determinants that can improve employees’ work quality, productivity, and organizational contribution. This study aims to analyze the influence of competence and career development on the performance of employees at the Secretariat of the Human Resources Development Agency of Transportation (BPSDM Perhubungan Jakarta). The research employed a quantitative approach with an associative research method. The population consisted of employees of the Secretariat of BPSDM Transportation Jakarta, with 104 respondents selected using a simple random sampling technique. Research data were collected through the distribution of Likert-scale questionnaires. The collected data were processed using SPSS version 25 and analyzed through multiple linear regression analysis. The findings imply that improving employees’ abilities and providing clear career opportunities can encourage greater motivation, professionalism, and responsibility at work. Organizations that consistently invest in competency enhancement and structured career advancement are more likely to create productive employees, strengthen institutional effectiveness, and support the achievement of long-term organizational goals sustainably.